Characterization of angiotensin II receptors in cultured adult rat cardiac fibroblasts. Coupling to signaling systems and gene expression. - Crabos, M (1994)
Cardiac hypertrophy is largely due to cardiac fibroblast growth and increased synthesis of extracellular matrix. This study has investigated the contribution of the vasoactive hormone, angiotensin II, toward this hypertrophic process. We have demonstrated that cultures of adult rat cardiac fibroblasts express AT1 but not AT2 receptors for angiotensin II. The ability of angiotensin II to stimulate phosphoinositide catabolism and to elevate intracellular calcium concentrations in these cells was blocked by losartan, a specific AT1 receptor antagonist, but not by the AT2 receptor antagonist CGP 42112. Exposure of adult cardiac fibroblasts to angiotensin II resulted in the induction of several growth-related metabolic events including c-fos protooncogene expression and increased synthesis of DNA, RNA, and protein. Angiotensin II was also found to induce collagen type I, alpha 1 chain transcript expression in cardiac fibroblasts as well as the synthesis and secretion of collagen by these cells. The data demonstrate that angiotensin II, via AT1 receptors, can stimulate cardiac fibroblast growth and increase collagen synthesis in cardiac tissue. Thus, angiotensin II may contribute toward the development of cardiac hypertrophy in conditions of hypertension that are associated with elevated concentrations of angiotensin II.